Mesenchymal Stem Cells Expressing Vasoactive Intestinal Peptide Ameliorate Symptoms in a Model of Chronic Multiple Sclerosis. Issue 5 (May 2013) - Cobo, Marién; Anderson, Per; Benabdellah, Karim; Toscano, Miguel G.; Muñoz, Pilar; García-Pérez, Angélica; Gutierrez, Iván; Delgado, Mario; Martin, Francisco
Multiple sclerosis (MS) is a severe debilitating disorder characterized by progressive demyelination and axonal damage of the central nervous system (CNS). Current therapies for MS inhibit the immune response and demonstrate reasonable benefits if applied during the early phase of relapsing–remitting MS (RRMS) while there are no treatments for patients that progress neither to the chronic phase nor for the primary progressive form of the disease. In this manuscript, we have studied the therapeutic efficacy of a cell and gene therapy strategy for the treatment of a mouse model of chronic MS [myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE)]. We used allogenic mesenchymal stem cells (MSCs) as a therapeutic tool and also as vehicle to deliver fully processed 3.3-kDa vasoactive intestinal peptide (VIP) to the peripheral immune organs and to the inflamed CNS. Intraperitoneal administrations of MSCs expressing VIP stopped progression and reduced symptoms when administered at peak of disease. The improvement in clinical score correlated with diminished peripheral T-cell responses against MOG as well as lower inflammation, lower demyelination, and higher neuronal integrity in the CNS. Interestingly, neither lentiviral vectors expressing VIP nor unmodified MSCs were therapeutic when administer at the peak of disease. The increased therapeutic effect of MSCs expressing VIP over unmodified MSCs requires the immunoregulatory and neuroprotective roles of both VIP and MSCs and the ability of the MSCs to migrate to peripheral lymph organs and the inflamed CNS.